Water Quality and Public Health Complaints in Surrounding Watoetoelis Sugar Mills - Yonar Trisna (JURNAL KESEHATAN LINGKUNGAN, 2018)
Industry as an integral part of the development of the country, more less having effect on the surrounding environment. Sugar factory as a part the industry also affects the quality of the surrounding environment through wastewater discharge at which water pollution control is required to achieve an ideal level of environmental health. PG Watoetoelis pollution control can be assessed from the water quality of its surrounding. This study aims to identify water quality and health complaints around PG Watoetoelis. This study is a descriptive observational study with cross sectional design. Primary data collection was conducted in July and August 2014, in the form of: interviews with questionnaires, environmental observation, inspection parameters of water samples of water bodies and wells in both upstream and downstream within 100 meters of the point of waste water discharge outlet Watoetoelis Sugar Factory. The results showed: the examination of water body samples found high levels of BOD5 in the amount of: 24.34 mg/L (upstream) and 24.15 mg/L (downstream), all wells water samples did not reveal any signs of physical and chemical pollution of water, respondents around PG Watoetoelis who with health complaints (9 of 17) experienced health complaints such as coughs of 7 people, and complained about the odor of the sugar factory pollution as many as 15 of 17 people. The conclusion of this study are bad water bodies quality, physical and chemical quality of the water samples of wells qualified, there are health complaints by respondents, but this can be due to other variables than physical and chemical parameters of the well water, such as; microbiology, hygiene and sanitation, or poor quality of the air in the environment, especially the residence location of the respondents.